Neurobiology and therapeutic applications of neurotoxins targeting transmitter release - Ovsepian, Saak V; O'Leary, Valerie B; Ayvazyan, Naira M; Al-Sabi, Ahmed; Ntziachristos, Vasilis; Dolly, James O (Pharmacology & therapeutics, 2019)
Synaptic transmission is a fundamental neurobiological process enabling exchange of signals between neurons as well as neurons and their non-neuronal effectors. The complex molecular machinery of the synaptic vesicle cycle and transmitter release has emerged and developed in the course of the evolutionary race, to ensure adaptive gain and survival of the fittest. In parallel, a generous arsenal of biomolecules and neuroactive peptides have co-evolved, which selectively target the transmitter release machinery, with the aim of subduing natural rivals or neutralizing prey. With advances in neuropharmacology and quantitative biology, neurotoxins targeting presynaptic mechanisms have attracted major interest, revealing considerable potential as carriers of molecular cargo and probes for meddling synaptic transmission mechanisms for research and medical benefit. In this review, we investigate and discuss key facets employed by the most prominent bacterial and animal toxins targeting the presynaptic secretory machinery. We explore the cellular basis and molecular grounds for their tremendous potency and selectivity, with effects on a wide range of neural functions. Finally, we consider the emerging preclinical and clinical data advocating the use of active ingredients of neurotoxins for the advancement of molecular medicine and development of restorative therapies.
Keywords: Synaptic Transmission; SNARE proteins; Tetanus toxin; Exocytosis; biologické toxiny; neurotransmiterové látky; nervový přenos; Therapeutic targeting; Botulinum neurotoxin; Neurotransmitter Agents; Neurotoxins; Animals; Toxins, Biological; lidé; Humans; zvířata; Drug delivery; Molecular medicine; Nano-carriers; neurotoxiny; Presynaptic